Remote sensing to evaluate geomorphological features for the environmental sensitivity to oil spills: Lower course of the river Piracicaba (SP) - Ribeiro, Daniela Ferreira [UNESP]; Lupinacci, Cenira Maria [UNESP]; Riedel, Paulina Setti [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
The Environmental Sensitivity Index mapping constitute an important tool for contingency planning and assessment of damage caused by oil spills. These maps widely used in coastal environments, where the methodology is well defined, present gaps for river environments. The main objective of this work is to contribute to the assessment of environmental sensitivity to oil of river environment by identifying and mapping geomorphological features of fluvial origin, carried out through visual interpretation of satellite images. Once identified, the features were analyzed for their sensitivity, considering parameters defined by international references, which are based on criteria such as degree of exposure, permeability, aspects related to river dynamics, as cumulative or erosive potential. The study area has a high sensitivity index of geomorphological features to oil spills due to the presence, for much of its length, of alluvial deposits, alluvial dikes and river terraces. It also highlights the presence of several tributaries rivers in the main channel, with low energy, which also sets a high sensitivity index. The regions with the lowest index are represented by areas close to urban areas, marked by built margins, with the presence of concreted walls and the presence of river sill. The geomorphological characterization through satellite images allows an expedited analysis, which is relevant in a country with continental dimensions as Brazil and can be detailed by fielwork in regions with greater complexity.
Sensoriamento remoto na avaliação das características geomorfológicas para a identificação da sensibilidade ambiental a derrames de óleo: Baixo curso do rio Piracicaba – SP
Keywords: Environmental sensitivity charts; Environmental sensitivity to oil; Geomorphology mapping